APOBEC3D excludes APOBEC3F from HIV-1 virions by competitive binding of RNA - Bhattacharjee, Shreoshri; Gaba, Amit; Chelico, Linda (Frontiers in Virology, 2024)
The human family of APOBEC3 enzymes are primarily studied as single-stranded DNA deoxycytidine deaminases that act as host restriction factors for a number of viruses and retroelements. The deamination of deoxycytidine to deoxyuridine causes inactivating mutations in target DNA and the nucleic acid binding ability may also cause deamination independent restriction. There are seven APOBEC3 enzymes in humans, named A-H, excluding E, each of which has restriction activity against a subset of viruses or retroelements. There are primarily four, APOBEC3D, APOBEC3F, APOBEC3G, and APOBEC3H that have been found to restrict replication of HIV-1, however their restriction activity varies and they have primarily been studied individually despite co-expression in the cells that HIV-1 infects. It is known that APOBEC3F hetero-oligomerizes with APOBEC3G and APOBEC3H and that this influences host restriction outcomes during HIV-1 infection in tissue culture. Here, we examined if APOBEC3F interacts with APOBEC3D and the functional outcomes. We found that APOBEC3D mRNA expression was similar to or higher than APOBEC3F mRNA in multiple donors, suggesting that the proteins would be co-expressed, allowing for interactions to occur. We determined that APOBEC3F and APOBEC3D interacted primarily through an RNA intermediate; however, this interaction resulted in APOBEC3D competitively excluding APOBEC3F from virions. Although HIV-1 restriction still occurred when APOBEC3F and APOBEC3D were co-expressed, it was due to primarily APOBEC3D-mediated deamination-independent restriction. The APOBEC3D-mediated exclusion of APOBEC3F from HIV-1 encapsidation could be recapitulated in vitro through RNA capture experiments in which APOBEC3D decreased or abrogated the ability of APOBEC3F to bind to HIV-1 protease or 5'UTR RNA, respectively. Overall, the data suggest that there are mechanisms at the protein level that segregate APOBEC3s into different virus particles.